Cryo‐protective effect of an ice‐binding protein derived from Antarctic bacteria. (26th December 2016) - Mangiagalli, Marco; Bar‐Dolev, Maya; Tedesco, Pietro; Natalello, Antonino; Kaleda, Aleksei; Brocca, Stefania; de Pascale, Donatella; Pucciarelli, Sandra; Miceli, Cristina; Braslavsky, Ido; Lotti, Marina
Abstract : Cold environments are populated by organisms able to contravene deleterious effects of low temperature by diverse adaptive strategies, including the production of ice binding proteins (IBPs) that inhibit the growth of ice crystals inside and outside cells. We describe the properties of such a protein ( Efc IBP) identified in the metagenome of an Antarctic biological consortium composed of the ciliate Euplotes focardii and psychrophilic non‐cultured bacteria. Recombinant Efc IBP can resist freezing without any conformational damage and is moderately heat stable, with a midpoint temperature of 66.4 °C. Tested for its effects on ice, Efc IBP shows an unusual combination of properties not reported in other bacterial IBPs. First, it is one of the best‐performing IBPs described to date in the inhibition of ice recrystallization, with effective concentrations in the nanomolar range. Moreover, Efc IBP has thermal hysteresis activity (0.53 °C at 50 μm ) and it can stop a crystal from growing when held at a constant temperature within the thermal hysteresis gap. Efc IBP protects purified proteins and bacterial cells from freezing damage when exposed to challenging temperatures. Efc IBP also possesses a potential N‐terminal signal sequence for protein transport and a DUF3494 domain that is common to secreted IBPs. These features lead us to hypothesize that the protein is either anchored at the outer cell surface or concentrated around cells to provide survival advantage to the whole cell consortium. Abstract : Efc IBP is an ice binding protein isolated from the bacterial consortium of the Antarctic ciliate Euplotes focardii . Efc IBP shows a to‐date uncommon combination of thermal hysteresis activity and high activity in inhibition of ice recrystallization.